2013
DOI: 10.1109/tlt.2013.26
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive and Intelligent Learning System for Physics Education

Abstract: Students tend to retain naı ¨ve understandings of concepts such as energy and force even after completing school and entering college. We developed a learning environment called the Virtual Physics System (ViPS) to help students master these concepts in the context of pulleys, a class of simple machines that are difficult to assemble and use in the real world. Several features make the ViPS noteworthy: it combines simulation and tutoring, it customizes tutoring to address common misconceptions, and it employs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Some of these efforts engage students in natural language dialogues [19,20] and introduce tools to help students solve quantitative problems [21,22]. Although such systems are more than a decade old, none are in wide use and their domains of applicability tend to be limited to one or two topics from introductory physics such as kinematics or Newton's laws, or a few concepts from electricity and magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these efforts engage students in natural language dialogues [19,20] and introduce tools to help students solve quantitative problems [21,22]. Although such systems are more than a decade old, none are in wide use and their domains of applicability tend to be limited to one or two topics from introductory physics such as kinematics or Newton's laws, or a few concepts from electricity and magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…experimental error), what Magin and Kanapathipillai (2000) describe as "unexpected clashes" (p. 352). Others, however, present evidence that supports non-traditional (virtual, remote) labs (NTL) as potentially sufficient replacements for TL (Cameron, 2003;Corter, Esche, Chassapis, Ma, & Nickerson, 2011;Lang, 2012;Myneni, Narayanan, Rebello, Rouinfar, & Pumtambekar, 2013;Pyatt & Sims, 2007;Zacharia & Olympiou, 2011). With NTL, students have multiple opportunities to access resources and a greater amount of time to complete specific laboratory activities, thus allowing repetition and modification, thereby fostering deeper learning (Charuk, 2010).…”
mentioning
confidence: 99%
“…With decades of research and development, ITS now have been built for various scientific domains such as physics [36], [22], [19], mathematics [9], [1], [41], chemistry [3], computer programming [16], [42], engineering [7], [26], medicine [13], [40], and so on. These studies showed that virtual manipulative through the ITS can significantly improve the learning.…”
Section: Intelligent Tutoring Systemmentioning
confidence: 99%